2007
DOI: 10.1007/s11136-007-9243-z
|View full text |Cite
|
Sign up to set email alerts
|

Deteriorating health status in Stockholm 1998–2002: results from repeated population surveys using the EQ-5D

Abstract: The observed deterioration in health status over time gives reason for concern. Investigation of reasons for the declining health status should be a research priority.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
62
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 14 publications
7
62
2
1
Order By: Relevance
“…We believe the results of this study support that hypothesis and also help to confirm findings in cross-sectional studies that showed lower scores in older age groups of children and adolescents [6,7]. Some studies in adult populations have showed similar declines in population-level HRQoL over substantial periods [34,35]. Pubertal development, an aspect that has only infrequently been analyzed in studies of HRQoL in children and adolescents, was found to have a strong impact on followup scores.…”
Section: Discussionsupporting
confidence: 84%
“…We believe the results of this study support that hypothesis and also help to confirm findings in cross-sectional studies that showed lower scores in older age groups of children and adolescents [6,7]. Some studies in adult populations have showed similar declines in population-level HRQoL over substantial periods [34,35]. Pubertal development, an aspect that has only infrequently been analyzed in studies of HRQoL in children and adolescents, was found to have a strong impact on followup scores.…”
Section: Discussionsupporting
confidence: 84%
“…8,10 We also found that the health status was lower in the elderly and female populations, which is similar to EQ-5D population health status studies in other countries. 10,13,[23][24][25] This study found housewives to have a lower quality of life than individuals with other occupations. This may be due to their low level of education, in most cases.…”
Section: Discussionmentioning
confidence: 69%
“…This pattern of HRQOL declining over time is consistent with findings from other investigators in the USA and abroad. [33][34][35][36] Understanding the deterioration of HRQOL in light of increasing life expectancy is crucial, given the aging of the population and the overarching goals of Healthy People. 10 A number of explanations have been provided for these findings, including an increased prevalence of obesity, increases in non-fatal conditions, and technological advances in medicine that offer lifesaving treatments for persons in poor health.…”
Section: Discussionmentioning
confidence: 99%